Climate sensitivity and geomorphological response of cirque glaciers from the late glacial to the Holocene, Sierra Nevada, Spain. (15th November 2020) - Palacios, David; Oliva, Marc; Gómez-Ortiz, Antonio; Andrés, Nuria; Fernández-Fernández, José M.; Schimmelpfennig, Irene; Léanni, Laëtitia; Team, A.S.T.E.R.
Abstract: Through a detailed geomorphological study, including thourough mapping of the geomorphic features as well as 10 Be Cosmic-Ray Exposure (CRE) dating, the geomorphological evolution of the Mulhacén cirque since the maximum ice extent of the last glacial cycle until nowadays was determined. This glacial cirque is shaped on the northern face of the Mulhacén peak (3479 m a.s.l. 37°03′12″N/3°18′41″W), Sierra Nevada, southern Spain. It includes several depositional and erosional glacial landforms that allowed reconstructing its environmental evolution since the last glacial cycle. Furthermore, the sequence of glacial oscillations from this site was compared to that of other cirques of the massif, evidencing that: (i) new glaciers formed in these cirques during the Younger Dryas (YD), and (ii) disappeared at 11.7 ± 1.0 ka. Depending on the altitude, orientation and height of the cirque walls, the final deglaciation of the cirques generated a diversity of landscapes, including a wide range of glacial and periglacial landforms, such as polished surfaces, sequences of moraines, proto-rock glaciers or large rock glacier systems. No glaciers existed in the Sierra Nevada during the Middle Holocene. Only the cirques whose summits exceed 3300 m, are north-exposed and whose walls exceed 300 m high (i.e. Mulhacén and Veleta) hosted glaciers during Neoglacial phases, including the Little Ice Age (LIA) (approx. 1300–1850 CE). During these periods, climate oscillations favoured the formation of small glaciers in these cirques, which generated large moraine systems with either one polygenic ridge or a sequence of spaced frontal arcs. The existence of glaciers impeded the formation of permafrost-related landforms, such as rock glaciers and protalus lobes until the end of the LIA, when they started to form. These results are compared with the deglacial evolution in 55 cirques from Iberian mountains as well as from glacial cirques from other mid-latitude mountains and subpolar regions. The chronology of their deglaciation as well as the landforms generated during glacial retreat followed similar patterns, with no significant differences at regional scale. For each mountain range, the geomorphological diversity existing in each cirque depends on the local topographic characteristics although they formed during the same climatic phases. Highlights: We examine the climatic sensitivity of geomorphic processes in glacial cirques. We focus on the variety of landforms in glacial cirques of Sierra Nevada, Spain. In this massif glacial cirques were deglaciated around 14 ka. Glaciers formed again during the Younger Dryas and disappeared around 11.7 ka. Most cirques of the North Hemisphere followed the same chronological sequence.